2013
DOI: 10.7314/apjcp.2013.14.11.6929
|View full text |Cite
|
Sign up to set email alerts
|

No Detection of Xenotropic Murine Leukemia Virus-Related Viruses in Prostate Cancer in Sanandaj, West of Iran

Abstract: Asian Pac J Cancer Prev, 14 (11), 6929-6933 IntroductionProstate cancer is the most common malignancy in men worldwide (Groom et al., 2012). The annual incidence rates of prostate cancer among Iranian population are dramatically higher than in other countries of Asia (Akbari et al., 2008). Multiple etiologies have been hypothesized for the cause of prostate cancers, including genetic defects, infectious agents and associated inflammation (Silverman et al., 2010). Identification of a potential virus as the caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…Hematologic malignancies are a common disease in Asian Pacific areas (Feng et al, 2013;Jiang et al, 2013;Karami et al, 2013;Khodabandehloo et al, 2013;Kooshyar et al, 2013;Li et al, 2013;Liu et al, 2013;Ozbas-Gerceker et al, 2013;Qin et al, 2013;Shan et al, 2013). As our present study confirmed, the level of serum ferritin of patients with hematologic malignancies was significantly increased.…”
Section: Discussionsupporting
confidence: 86%
“…Hematologic malignancies are a common disease in Asian Pacific areas (Feng et al, 2013;Jiang et al, 2013;Karami et al, 2013;Khodabandehloo et al, 2013;Kooshyar et al, 2013;Li et al, 2013;Liu et al, 2013;Ozbas-Gerceker et al, 2013;Qin et al, 2013;Shan et al, 2013). As our present study confirmed, the level of serum ferritin of patients with hematologic malignancies was significantly increased.…”
Section: Discussionsupporting
confidence: 86%
“…We previously did not detect xenotropic murine leukemia virus -related virus (XMRV) in samples either from prostate cancer or benign prostate hyperplasia (17).…”
Section: Discussionmentioning
confidence: 99%